A hydrophilic modified polysulfone hollow fiber nanofiltration membrane and its use
Through the chemical treatment of hydrophilic modified polysulfone materials, the hydrophilicity and negative chargeability of the hollow fiber nanofiltration membrane are improved, and the existing membrane retention efficiency and poor permeability are solved, achieving efficient inorganic salt retention and good thermal stability.
Patent Information
- Application Number
- CN202411918808.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing hollow fiber nanofiltration membrane has strong hydrophobicity, low interception efficiency, and insufficient surface charge, resulting in poor permeability, which affects its application prospects in high-salt wastewater treatment and other fields.
Hydrophilic modified polysulfone materials are used to form an excellent negatively charged hollow fiber nanofiltration membrane by configuring a cast membrane liquid, preparing a hollow base membrane and chemically treating it.
The permeability flux and retention of the membrane were significantly improved, especially the retention rate of Na2SO4 reached 98.3%, and it had good long-term thermal stability and selective retention performance.
Smart Images

Figure CN119345931B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer membrane materials, in particular to a hydrophilic modified polysulfone hollow fiber nanofiltration membrane and application thereof. Background Art
[0002] Water is essential to human health. However, wastewater is increasing, and much of it contains high levels of Cl - , SO4 2- , Na + , Ca 2+ Nanofiltration membrane technology is a separation technology that can effectively intercept 200-1000 Dalton substances. It has unique advantages in removing suspended solids, dissolved organic matter, heavy metal ions, etc. from water, and is widely used in high-salt wastewater treatment, pharmaceuticals, chemical industry and other fields.
[0003] Compared with traditional rolled nanofiltration membranes, hollow fiber nanofiltration membranes have attracted more and more attention due to their good self-supporting properties, high filling density, large specific surface area and wide water inlet flow channel. There are many types of hollow fiber nanofiltration membranes, but they are usually made of highly hydrophobic polysulfone polymer materials. The problems of insufficient retention of hydrophobic substances and serious pollution have greatly affected their application prospects. In addition, due to the low surface charge, many hollow fiber nanofiltration membranes have problems such as low retention rate and poor permeability. Summary of the invention
[0004] In view of the above problems existing in the prior art, the purpose of the present invention is to design and provide a technical solution of a hydrophilically modified polysulfone hollow fiber nanofiltration membrane and its use. The hollow fiber nanofiltration membrane has excellent hydrophilic modification, permeation flux, retention and long-term thermal stability. The water contact angle of the hollow fiber nanofiltration membrane is 66.0±1.8°, and the membrane pure water permeation flux is 33.2±1.1 L∙m -2 ∙h -1 (0.4MPa), the Na2SO4 retention rate is as high as 98.3±1.2% (0.4MPa), 30%≦NaCl retention rate≦40% (0.4MPa), and the optimal retention rate can reach 38.5±0.2%.
[0005] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is characterized by being prepared by the following method:
[0006] 1) preparing a casting solution: based on the total mass of the casting solution, 15-25wt% of a film-forming polymer, 4-12wt% of a hydrophilic additive, and 6-13wt% of a porogen are mixed and added to a 50-75wt% solvent, wherein the film-forming polymer is selected from at least one of polysulfone materials, including PSF (polysulfone), PES (polyethersulfone), PPSU (polyphenylene sulfone), SPSF (sulfonated polysulfone), SPES (sulfonated polyethersulfone), SPPSU (sulfonated polyphenylene sulfone), preferably PES; the hydrophilic additive is at least one of the homologous compounds of perfluorohexylsulfonamidopropyltriethoxysilane (PFSS) with a carbon chain length of 3-8, preferably PFSS, and the carbon chain length directly affects the Π-F effect between the additive and the film-forming polymer, and is an important factor affecting the membrane structure; heating and stirring in a water bath, mixing evenly, and degassing to obtain a casting solution;
[0007] 2) Preparation of hollow base membrane: The casting solution is subjected to non-solvent induced phase separation method to prepare the hollow base membrane;
[0008] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane is chemically treated to obtain a hydrophilically modified polysulfone hollow fiber nanofiltration membrane.
[0009] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is characterized in that in step 1), the membrane-forming polymer is 18-22wt%, the hydrophilic auxiliary agent is 6-10wt%, the porogen is 8-11wt%, and the solvent is 55-70wt%.
[0010] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is characterized in that in step 1), the porogen is at least one of polyethylene glycol (PEG) and polyvinyl pyrrolidone (PVP) of different molecular weights, preferably at least one of PEG400, PEG600, PEG800, PEG1000, PEG1500, PVPK17, PVPK30, and PVPK90, preferably PEG with a molecular weight of less than 600. The molecular weight of the porogen directly affects the size of the pore size. The use of a porogen with a smaller molecular weight makes it easier to form a smaller pore size in the fiber, improve the porosity, improve the mechanical properties of the membrane, and enhance the separation efficiency of the separation membrane.
[0011] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is characterized in that in step 1), the solvent is at least one of dimethylacetamide (DMAC), dimethylformamide (DMF), and N-methylpyrrolidone (NMP). The type of solvent not only has an important influence on the rheological properties of the casting solution and the stability of the spinning process, but is also a key factor affecting the phase transformation process and pore structure.
[0012] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is characterized in that in step 1), the water bath stirring temperature is 60-80°C, the stirring time is 2-4 h, and the stirring speed is 150-250 r / min; preferably, the water bath stirring temperature is 65-70°C, the stirring time is 2.5-3 h, and the stirring speed is 200-220 r / min. By adjusting the stirring conditions, the rheological properties of the casting solution are controlled to ensure the smooth progress of the preparation process.
[0013] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is characterized in that the specific method in step 2) is: the casting liquid is introduced into a coagulation bath after passing through a spinneret containing a core liquid to obtain a primary fiber membrane, and the primary fiber membrane is rinsed to obtain a hollow fiber base membrane; the core liquid is deionized water, the coagulation bath is a NaOH aqueous solution, the rinsing bath is deionized water, the coagulation bath temperature is 25-40°C, and the rinsing bath temperature is 40-60°C; preferably, the coagulation bath temperature is 30-35°C, and the rinsing bath temperature is 45-50°C. The pH value of the NaOH aqueous solution is 7-10, preferably 9. By controlling the composition, temperature and alkalinity of the coagulation bath, the decomposition degree of the hydrophilic additive is regulated, thereby optimizing the negative charge and hydrophilicity of the membrane surface.
[0014] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is characterized in that the chemical treatment process in step 3) is specifically as follows: the hollow base membrane prepared in step 2) is placed in a glutaraldehyde aqueous solution at a certain temperature for a certain period of time for chemical crosslinking, and the chemical crosslinking temperature is 30-40°C, preferably 35°C; the mass fraction of the glutaraldehyde aqueous solution is 5-25wt%.
[0015] The chemical cross-linking time is 1.5-2.5 hours, preferably 2 hours.
[0016] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane is used in improving the quality of tap water.
[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0018] The present invention blends PFSS homologous compounds with good hydrophilic modification and negative charge with polysulfone polymers, hydrolyzes the sulfonyl groups in the PFSS homologous compounds in an alkaline environment and converts them into negatively charged sulfonic acid groups, thereby preparing a negatively charged hollow fiber nanofiltration membrane with excellent performance, which significantly improves the hydrophilicity and negative charge of the polysulfone membrane.
[0019] The present invention utilizes the strong π-F interaction between the carbon fluorine chain carried by the PFSS homologous compounds and the benzene ring in the polysulfone polymer to strengthen the molecular coupling of the two, and at the same time, with the help of the good self-crosslinking reaction of the PFSS homologous compounds, a physical interlaced network structure is formed, thereby improving the structural stability of the separation layer in both directions.
[0020] The present invention utilizes aldehyde solution to partially cross-link the sulfonic acid groups obtained by hydrolyzing PFSS homologous compounds on the membrane surface, thereby promoting the densification of the separation layer on the membrane surface and forming a nanofiltration layer. The retention performance of different inorganic salts shows a certain selectivity, and the retention performance is R (Na2SO4)>R (MgSO4)>R (MgCl2)>R (NaCl).
[0021] The hydrophilic modified polysulfone hollow fiber nanofiltration membrane of the present invention has high heavy metal ion interception efficiency and is effective for Cu 2+ and Co 2+ The interception rate can reach 97.5% and 96.2% respectively, which can be used to improve the quality of tap water.
[0022] The preparation method of the present invention has a simple operation process and is environmentally friendly, and effectively avoids complicated operations and the use of expensive materials in the membrane preparation process. It is convenient for large-scale production in practical applications and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The surface contact angle test results of the hydrophilic modified polysulfone hollow fiber-based membrane and the nanofiltration membrane prepared in each embodiment and comparative example are shown;
[0024] Figure 2 The pure water flux test results of the hydrophilic modified polysulfone hollow fiber-based membrane and the nanofiltration membrane prepared in each embodiment and comparative example are shown;
[0025] Figure 3 The figures are test results of the inorganic salt solution retention performance of the hydrophilic modified polysulfone hollow fiber nanofiltration membranes prepared in the embodiments and comparative examples;
[0026] Figure 4 The figure is a test result of the heavy metal ion rejection performance of the hydrophilic modified polysulfone hollow fiber nanofiltration membrane prepared in Experimental Example 1 and Example 1;
[0027] Figure 5 This is a graph showing the long-term stability test results of the flux and Na2SO4 and NaCl retention efficiency of the hydrophilic modified polysulfone hollow fiber nanofiltration membrane prepared in Example 1. DETAILED DESCRIPTION
[0028] The present invention will be further described below by way of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods and reagents used in the examples are, unless otherwise stated, conventional methods and reagents in the art.
[0029] Example 1
[0030] 1) Prepare the casting solution: based on the total mass of the casting solution, add 20wt% PES, 12wt% PFSS, and 13wt% PEG (Mr: 400) to 55wt% DMAC, heat in a 60°C water bath with stirring for 2.5h at a stirring speed of 200r / min, mix well, and degas to obtain the casting solution;
[0031] 2) preparing a hollow base membrane: the casting solution obtained in step 1) is passed through a spinneret containing a core liquid of water and then introduced into a NaOH solution at 25° C. and a pH value of 9 to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 50° C. bath to obtain a base membrane;
[0032] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane prepared in step 2) was placed in a glutaraldehyde aqueous solution at 35° C. for 2 hours for chemical cross-linking to obtain the hollow fiber nanofiltration membrane. The obtained membrane product was marked as M-1.
[0033] The mass fraction of the glutaraldehyde aqueous solution is 20wt%.
[0034] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate were as follows: Figure 1-Figure 3 shown.
[0035] Example 2
[0036] 1) Prepare the casting solution: based on the total mass of the casting solution, add 25wt% of PES, 12wt% of PFSS, and 13wt% of PVP into 50wt% of NMP, heat and stir in a water bath at 55°C for 3h at a stirring speed of 200r / min, mix evenly, and degas to obtain the casting solution;
[0037] 2) preparing a hollow base membrane: the casting solution obtained in step 1) is passed through a spinneret containing a core liquid of water and then introduced into a NaOH solution at 30° C. and a pH value of 9 to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 50° C. bath to obtain a base membrane;
[0038] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane prepared in step 2) was placed in a glutaraldehyde aqueous solution at 35° C. for 2 hours for chemical cross-linking to obtain the hollow fiber nanofiltration membrane. The obtained membrane product was marked as M-2.
[0039] The mass fraction of the glutaraldehyde aqueous solution is 22wt%.
[0040] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate were as follows: Figure 1-Figure 3 shown.
[0041] Example 3
[0042] Preparation of casting solution: Based on the total mass of the casting solution, 18wt% of PSF, 10wt% of PFSS, and 13wt% of PEG (Mr=600) were mixed and added into 69wt% of NMP, heated in a water bath at 60°C with stirring for 3h at a stirring speed of 200r / min, mixed evenly, and degassed to obtain a casting solution;
[0043] 2) preparing a hollow base membrane: the casting solution obtained in step 1) is passed through a spinneret containing a core liquid of water and then introduced into a NaOH solution at 32° C. and a pH value of 9 to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 45° C. bath to obtain a base membrane;
[0044] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane prepared in step 2) was placed in a glutaraldehyde aqueous solution at 35° C. for 2 hours for chemical cross-linking to obtain the hollow fiber nanofiltration membrane. The obtained membrane product was marked as M-3.
[0045] The mass fraction of the glutaraldehyde aqueous solution is 25wt%.
[0046] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate were as follows: Figure 1-Figure 3 shown.
[0047] Example 4
[0048] Preparation of casting solution: Based on the total mass of the casting solution, 23wt% of PPSF, 8wt% of PFSS, and 7wt% of PEG (Mr=600) were mixed and added into 62wt% of NMP, heated in a 50°C water bath with stirring for 3h at a stirring speed of 200r / min, mixed evenly, and degassed to obtain a casting solution;
[0049] 2) preparing a hollow base membrane: the casting solution obtained in step 1) is passed through a spinneret containing a core liquid of water and then introduced into a NaOH solution at 35° C. and a pH value of 9 to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 47° C. bath to obtain a base membrane;
[0050] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane prepared in step 2) was placed in a glutaraldehyde aqueous solution at 35° C. for 2 hours for chemical cross-linking to obtain the hollow fiber nanofiltration membrane. The obtained membrane product was marked as M-4.
[0051] The mass fraction of the glutaraldehyde aqueous solution is 15wt%.
[0052] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate were as follows: Figure 1-Figure 3 shown.
[0053] Comparative Example 1-2
[0054] 1) Prepare the casting solution: based on the total mass of the casting solution, add 20wt% of PES, a certain amount of PFSS, and 13wt% of PEG (Mr: 400) to DMAC, heat and stir in a 60°C water bath for 4 h at a stirring speed of 200 r / min, mix evenly, and degas to obtain the casting solution;
[0055] The PFSS contents are respectively 0 (Comparative Example 1) and 12 wt % (Comparative Example 2).
[0056] The DMAC contents are 77 wt % (Comparative Example 1) and 56 wt % (Comparative Example 2).
[0057] Preparation of hollow base membrane: the casting solution obtained in step 1) is introduced into a 25° C. coagulation bath after passing through a spinneret containing a core liquid of water to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 50° C. bath to obtain a base membrane;
[0058] The coagulation baths are respectively a NaOH aqueous solution with a pH of 9 (Comparative Example 1) and an aqueous solution (Comparative Example 2).
[0059] Preparation of hollow fiber nanofiltration membrane: placing the hollow base membrane obtained in step 2) in a cross-linking bath at 35°C for 2 hours for chemical cross-linking to obtain the hollow fiber nanofiltration membrane. The membrane products obtained in Comparative Examples 1-2 are marked as C-1 and C-2, respectively.
[0060] The cross-linking baths are respectively a glutaraldehyde aqueous solution with a mass fraction of 20 wt % (Comparative Example 1) and a pure aqueous solution (Comparative Example 2).
[0061] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate were as follows: Figure 1-Figure 3 shown.
[0062] The difference between Comparative Example 1 and Example 1 is that the casting solution of Example 1 contains a hydrophilic additive PFSS, while the casting solution of Comparative Example 1 does not contain PFSS. The results show that compared with Comparative Example 1, the flux, hydrophilicity, and Na2SO4, MgSO4 and other interception efficiencies of the hollow base membrane and hollow fiber nanofiltration membrane in Example 1 are better than those of the corresponding membrane samples in Comparative Example 1. And the various indicators measured in Example 1 are all in a more stable state compared with Comparative Example 1.
[0063] The difference between Comparative Example 2 and Example 1 is that the coagulation bath of Example 1 is a NaOH aqueous solution with a pH of 9, and the cross-linking bath is a 20wt% glutaraldehyde solution, while the coagulation bath and the cross-linking bath of the comparative example are both pure aqueous solutions, that is, Comparative Example 2 uses pure water coagulation and is not subjected to chemical cross-linking operation. The results show that the flux, hydrophilic modification and each inorganic salt retention efficiency of the hollow base membrane and hollow fiber nanofiltration membrane in Comparative Example 2 are all lower than those of the corresponding membrane samples in Example 1 and Comparative Example 1. Specifically, it is inferior to Example 1 but better than Comparative Example 1. It shows that the addition of the hydrophilic additive PFSS and the combined process of alkaline hydrolysis and chemical treatment of glutaraldehyde solution are beneficial to improving the membrane separation performance.
[0064] Comparative Example 3
[0065] 1) Prepare the casting solution: based on the total mass of the casting solution, add 20wt% PES, 12wt% PFSS, and 8wt% PEG (Mr: 400) to 60wt% DMAC, heat and stir in a 60°C water bath for 4 h at a stirring speed of 200 r / min, mix evenly, and degas to obtain the casting solution;
[0066] 2) preparing a hollow base membrane: the casting solution obtained in step 1) is passed through a spinneret containing a core liquid of water and then introduced into a NaOH solution at 25° C. and a pH value of 9 to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 50° C. bath to obtain a base membrane;
[0067] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane prepared in step 2) was placed in a glutaraldehyde aqueous solution at 35° C. for 2 hours for chemical cross-linking to obtain the hollow fiber nanofiltration membrane. The obtained membrane product is marked as C-3.
[0068] The mass fraction of the glutaraldehyde aqueous solution is 20wt%.
[0069] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate were as follows: Figure 1-Figure 3 shown.
[0070] The difference between Comparative Example 3 and Example 1 is that the pore-forming agent PEG content in Example 1 is 13wt%, and the pore-forming agent PEG content in Comparative Example 3 is 8wt%. The results show that compared with Comparative Example 3, the flux, hydrophilic modification and inorganic salt retention efficiency of the hollow base membrane and hollow fiber nanofiltration membrane in Example 1 are better than those of the corresponding membrane samples in Comparative Example 1.
[0071] Comparative Examples 4-5
[0072] 1) Prepare the casting solution: based on the total mass of the casting solution, add 20wt% of PES, 12wt% of the hydrophilic additive, and 13wt% of PEG (Mr: 400) to 55wt% of DMAC, heat and stir in a water bath at 60°C for 4h at a stirring speed of 200r / min, mix evenly, and degas to obtain the casting solution;
[0073] The hydrophilic adjuvants are perfluorobutylsulfonamidopropyltriethoxysilane and perfluoroheptylsulfonamidopropyltriethoxysilane.
[0074] 2) preparing a hollow base membrane: the casting solution obtained in step 1) is passed through a spinneret containing a core liquid of water and then introduced into a NaOH solution at 25° C. and a pH value of 9 to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 50° C. bath to obtain a base membrane;
[0075] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane prepared in step 2) was placed in a glutaraldehyde aqueous solution at 35° C. for 2 hours for chemical crosslinking to obtain the hollow fiber nanofiltration membrane. The membrane products obtained in Comparative Examples 4-5 are marked as C-4 and C-5.
[0076] The mass fraction of the glutaraldehyde aqueous solution is 20wt%.
[0077] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate of comparative examples 4-5 were as follows: Figure 1-Figure 3 shown.
[0078] The difference between Comparative Examples 4 and 5 and Example 1 is that the hydrophilic additive in Example 1 is PFSS, while the hydrophilic additives in Comparative Examples 4 and 5 are perfluorobutylsulfonamidopropyltriethoxysilane and perfluoroheptylsulfonamidopropyltriethoxysilane, respectively. The results show that the NaCl retention rate of Example 1 is much higher than that of Comparative Examples 4 and 5.
[0079] Comparative Examples 6-7
[0080] 1) Prepare the casting solution: based on the total mass of the casting solution, add 20wt% PES, 12wt% PFSS, and 13wt% PEG (Mr: 400) to 55wt% DMAC, heat in a water bath at 60°C with stirring for 4h at a stirring speed of 200r / min, mix well, and degas to obtain the casting solution;
[0081] 2) preparing a hollow base membrane: the casting solution obtained in step 1) is passed through a spinneret containing a core liquid of water and then introduced into a NaOH solution at 25° C. and a pH value of 9 to obtain a primary fiber membrane. The primary fiber membrane is rinsed in a 50° C. bath to obtain a base membrane;
[0082] 3) Preparation of hollow fiber nanofiltration membrane: The hollow base membrane prepared in step 2) was placed in a glutaraldehyde aqueous solution at 35° C. for 2 hours for chemical crosslinking to obtain the hollow fiber nanofiltration membrane. The membrane products obtained in Comparative Examples 6 and 7 are marked as C-6 and C-7, respectively.
[0083] The mass fractions of the glutaraldehyde aqueous solution are respectively 1 wt % (Comparative Example 6) and 30 wt % (Comparative Example 7).
[0084] 4) Membrane fiber test: 8 groups of hollow base membranes and hollow fiber nanofiltration membrane fibers were tested. The average contact angle, pure water flux and inorganic salt retention rate of comparative examples 6-7 were as follows: Figure 1-Figure 3 shown.
[0085] The difference between Comparative Examples 6 and 7 and Example 1 is that the mass fraction of the glutaraldehyde aqueous solution in Example 1 is 20wt%, and the mass fractions of the glutaraldehyde aqueous solution in Comparative Examples 6 and 7 are 5wt% and 30wt%, respectively. The results show that the flux and NaCl retention rate of the hollow fiber nanofiltration membrane in Example 1 are between Comparative Examples 6 and 7, specifically, the flux is better than that of Example 7, and the retention rate is better than that of Example 6.
[0086] The beneficial effects of the present application are further demonstrated by corresponding test data below.
[0087] Test 1: Water contact angle test on membrane surface
[0088] In this experiment, the water contact angle of the hollow base membrane and hollow fiber nanofiltration membrane prepared in each embodiment and comparative example was tested to characterize the hydrophilic modification change of the membrane. The results are as follows: Figure 1 As shown. The water contact angle values of the base membrane and nanofiltration membrane surfaces prepared in each group are detailed in Table 1. The results show that the water contact angles of the nanofiltration membrane surfaces prepared in Examples 1-4 are 66.8±1.3°, 67.1±1.5°, 63.5±1.0° and 68.4±1.3°, respectively; the water contact angles of the nanofiltration membrane surfaces prepared in Comparative Examples 1-7 are 82.3±4.1°, 74.2±3.2°, 73.4±2.4°, 66.4±3.0°, 67.5±2.8°, 65.1±2.2° and 63.2±3.2°, respectively. It can be seen that compared with Comparative Example 1, the addition of hydrophilic additives such as PFSS in Examples 1-4 and Comparative Examples 2-7 and the double chemical treatment process of NaOH and glutaraldehyde aqueous solution effectively improve the hydrophilicity of the membrane surface, and the water contact angle is significantly reduced.
[0089] Table 1 Water contact angle and pure water flux test table of each group of hollow base membrane and nanofiltration membrane surface
[0090]
[0091] Test 2: Pure water flux test
[0092] At room temperature and 4 bar pressure, the hollow base membrane and hollow fiber nanofiltration membrane prepared in the above examples and comparative examples were pre-pressed with pure water for 30 minutes to achieve a stable flux, and then a pure water flux test was performed at 4 bar pressure. The calculation formula is as follows:
[0093] P = V / (A × t), V represents the permeation volume, m 3 ; A represents the effective area of the membrane, m 2 ; t represents the filtering time, s, the results are shown in Figure 2 As shown in Table 1. The results show that the hollow fiber nanofiltration membrane prepared by the scheme recorded in the present invention has a high pure water flux, and the flux of each membrane exceeds 28L∙m -2 ∙h -1 The pure water flux of the membrane samples in Examples 1-4 was 33.2±1.1 L∙m -2 ∙h -1 , 28.9±2.6L∙m -2 ∙h -1 、31.3±2.3L∙m -2 ∙h -1 , 28.2±1.9L∙m -2 ∙h -1 The pure water fluxes of Comparative Examples 1-7 were 17.3±2.2L∙m -2 ∙h -1 , 24.7±2.3L∙m -2 ∙h -1 , 20.6±3.1L∙m -2 ∙h -1 , 23.6±1.4L∙m -2 ∙h -1 , 19.4±2.2L∙m -2 ∙h -1 , 37.2±1.2L∙m -2 ∙h -1 and 15.5±2.2L∙m -2 ∙h -1 .
[0094] Further analysis shows that the addition of PFSS and its homologous compounds and the treatment with NaOH solution effectively improve the hydrophilicity of the hollow fiber nanofiltration membrane, thereby increasing the water flux of the hollow fiber nanofiltration membrane, and as the PFSS content increases from 0 to 12wt%, the membrane water flux gradually increases. In addition, during the chemical treatment process, the increase in the mass fraction of glutaraldehyde solution is conducive to strengthening the degree of chemical cross-linking, increasing the density of the membrane surface, and reducing the membrane flux.
[0095] Test 3: Inorganic salt retention efficiency test
[0096] At room temperature and 4 bar pressure, the hollow fiber nanofiltration membranes prepared in each embodiment and comparative example were pre-pressed with pure water for 30 minutes to achieve a stable flux, and then 1 g / L of sodium chloride, magnesium chloride, sodium sulfate, and magnesium sulfate were filtered respectively. The selective permeability of each hollow fiber nanofiltration membrane was characterized by the removal rate of salt in the four solutions. The calculation formula of the membrane retention rate is as follows:
[0097] R = [1- (KP / KR)] × 100%, where KP and KR represent the conductivity of the salt solution in the permeate and stock solution, respectively. Figure 3 As shown in Table 2. It can be observed that, compared with Comparative Example 1 without adding a hydrophilic additive and Comparative Example 2 with only adding a hydrophilic additive but without performing NaOH hydrolysis and glutaraldehyde chemical crosslinking, the interception efficiency of each hydrophilic modified hollow fiber nanofiltration membrane is greatly improved, and the interception efficiency of Na2SO4 and MgSO4 is more than 90%, and the interception efficiency of NaCl can reach up to 40%. This is because the chemical operation of hydrophilic additives and hydrolysis crosslinking is conducive to improving the negative charge of the membrane surface. In addition, the interception performance of each nanofiltration membrane has good selectivity, which is specifically manifested as R (Na2SO4)>R (MgSO4)>R (MgCl2)>R (NaCl). It can be seen that the hydrophilic modified polysulfone hollow fiber nanofiltration membrane prepared by the present invention is a negatively charged membrane with excellent selectivity.
[0098] Table 2 Inorganic salt retention rate test table of each group of membrane samples
[0099]
[0100] Test 4: Heavy metal ion retention efficiency
[0101] According to the method of Experiment 3, the nanofiltration membrane prepared in Example 1 was subjected to a heavy metal ion filtration experiment. The test results are as follows: Figure 4 shown. Figure 4 It shows that the hydrophilic modified polysulfone hollow fiber nanofiltration membrane prepared by the present invention has good performance on Cu 2+ and Co 2+ The retention rates of the two catalysts can reach 97.5% and 96.2% respectively, which shows good heavy metal ion separation performance.
[0102] Test 5: Long-term thermal stability test
[0103] The performance stability of the hollow fiber nanofiltration membrane was verified by long-term filtration experiments. Taking Example 1 as an example, a long-term filtration experiment was performed on it to characterize the performance stability of the prepared hydrophilic modified polysulfone hollow fiber nanofiltration membrane. Specifically, deionized water, Na2SO4 (1g / L) and NaCl (1g / L) were used as feed solutions, respectively, at 4 bar for 84 hours, and the membrane permeability and salt retention rate were measured every 2 hours. The results are shown in Figure 5As shown in Table 3. It can be seen that the membrane shows a high and stable Na2SO4 rejection rate (~98.0%) and a relatively low NaCl rejection rate (~35.3%). Within 84 hours, the water permeation flux of the hollow fiber nanofiltration membrane prepared by the present invention increased from 32.8 L∙m -2 ∙h -1 Down to 31.1L∙m -2 ∙h -1 , has an efficient and durable long-term separation process, and shows extremely high selectivity for Na2SO4 and NaCl, indicating its excellent performance stability and structural stability.
[0104] Table 3 Long-term stability test table of water flux and salt rejection of M-1 sample
[0105] Time (h) <![CDATA[Water flux (L∙m -2 ∙h -1 ).]]> <![CDATA[Na2SO4 rejection rate (%)]]> NaCl retention rate (%) 8 32.8±1.2 98.9±0.9 36.5±1.7 16 32.4±1.8 99.0±1.7 35.1±1.8 24 32.1±1.6 97.9±2.0 37.0±1.2 32 32.3±2.1 99.0±2.1 36.5±1.6 40 31.6±1.5 99.8±3.4 34.7±2.0 48 32.2±1.5 98.9±3.7 35.5±2.1 56 31.5±1.3 97.9±1.9 35.4±1.7 64 31.7±1.3 98.9±2.5 35.0±2.1 72 31.5±1.2 98.8±3.5 36.8±1.5 80 31.1±2.5 98.9±1.0 34.6±1.5
[0106] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the above-described embodiments are only a preferred implementation scheme of the present invention, which is only for illustrating the technical concept and features of the present invention, and cannot be used to limit the protection scope of the present invention. All equivalent technologies that are equivalently replaced or modified according to the concept of the present invention are protected by the present invention.
Claims
1. A hydrophilic modified polysulfone hollow fiber nanofiltration membrane, characterized in that Prepared by the following method: 1) preparing a casting solution: based on the total mass of the casting solution, 15-25wt% of a film-forming polymer, 4-12wt% of a hydrophilic additive, and 6-13wt% of a porogen are mixed and added into 50-75wt% of a solvent, wherein the film-forming polymer is at least one polysulfone material, and the hydrophilic additive is at least one homologous compound of perfluorohexylsulfonamidopropyltriethoxysilane with a carbon chain length of 3-8, and the mixture is heated in a water bath and stirred to be uniformly mixed, and degassed to obtain a casting solution; 2) Preparation of hollow base membrane: The casting solution is subjected to non-solvent induced phase separation method to prepare the hollow base membrane; The specific method in step 2) is: the casting liquid is passed through a spinneret containing a core liquid and then introduced into a coagulation bath for phase inversion and initial hydrolysis and crosslinking to obtain a primary fiber membrane, and the primary fiber membrane is rinsed in a bath to obtain a hollow fiber base membrane; the core liquid is deionized water, and the coagulation bath is a NaOH aqueous solution; 3) Preparation of hollow fiber nanofiltration membrane: chemically treating the hollow base membrane to obtain a hydrophilic modified polysulfone hollow fiber nanofiltration membrane; The chemical treatment process in step 3) is specifically as follows: placing the hollow base membrane prepared in step 2) in a glutaraldehyde aqueous solution at a certain temperature for a certain period of time for chemical cross-linking.
2. A hydrophilic modified polysulfone hollow fiber nanofiltration membrane as claimed in claim 1, characterized in that In step 1), the film-forming polymer is 18-22 wt%, the hydrophilic additive is 6-10 wt%, the porogen is 8-11 wt%, and the solvent is 55-70 wt%.
3. A hydrophilic modified polysulfone hollow fiber nanofiltration membrane as claimed in claim 1, characterized in that In step 1), the film-forming polymer is at least one of polysulfone, polyethersulfone, polyphenylene sulfone, sulfonated polysulfone, sulfonated polyethersulfone and sulfonated polyphenylene sulfone.
4. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 1, characterized in that In step 1), the porogen is at least one of polyethylene glycol and polyvinyl pyrrolidone with different molecular weights.
5. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 1, characterized in that In step 1), the solvent is at least one of dimethylacetamide, dimethylformamide and N-methylpyrrolidone.
6. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 1, characterized in that In step 1), the stirring temperature of the water bath is 60-80°C, the stirring time is 2-4h, and the stirring speed is 150-250r / min.
7. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 1, characterized in that In step 2), the rinsing bath is deionized water, the coagulation bath temperature is 25-40°C, and the rinsing bath temperature is 40-60°C.
8. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 1, characterized in that In step 3), the chemical cross-linking temperature is 30-40° C., and the chemical cross-linking time is 1.5-2.5 h.
9. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 8, wherein the mass fraction of the aqueous solution of glutaraldehyde is 5-25wt%.
10. Application of the hydrophilic modified polysulfone hollow fiber nanofiltration membrane as claimed in claim 1 in improving water quality in the tap water industry.
11. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 4, characterized in that: The porogen is at least one of PEG400, PEG600, PEG800, PEG1000, PEG1500, PVPK17, PVPK30, and PVPK90.
12. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 6, characterized in that: The water bath stirring temperature is 65-70°C, the stirring time is 2.5-3h, and the stirring speed is 200-220r / min.
13. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 7, characterized in that: The temperature of the coagulation bath is 30-35° C., the temperature of the rinsing bath is 45-50° C., and the pH value of the NaOH aqueous solution is 9.
14. The hydrophilic modified polysulfone hollow fiber nanofiltration membrane according to claim 8, characterized in that: The chemical cross-linking temperature was 35°C and the chemical cross-linking time was 2 h.
Citation Information
Patent Citations
One-step formed hollow fiber nanofiltration membrane filament and preparation method thereof
CN110917911A
Cu-AMO composite membrane for degrading quinolone antibiotics and application of Cu-AMO composite membrane
CN118454483A